Excess Volume, Viscosity and Speed of Sound for p-Xylene with 2-Nitrotoluene System at 298.15, 303.15 and 313.15 K - Kapoor, Seema; Rattan, V.K. (Asian Journal of Chemistry, 2010)
Excess volume (VE), viscosity and speed of sound data at 298.15, 303.15 and 313.15 K were measured for binary system formed by p-xylene with 2-nitrotoluene. Excess volumes were measured directly using a dilatometer1. The excess properties such as excess volume (VE), deviation in viscosity (Δη) and excess compressibility (KES ) are discussed in terms of molecular interactions between like and unlike molecules. All the excess properties have been fitted to the Redlich-Kister equation.